Modernizing wholesalers and guava farmers in Mexico - Hernandez, Ricardo; Berdegué, Julio; Reardon, Thomas (Wiley, 2015)
This article focuses on the rapid development of the “modernizing wholesale” channel, with a study of guava traders and farmers in Mexico. This adds to a literature on modernization of food markets that has focused primarily on exports, supermarkets, and large processors and addressed less wholesale in general and rarely modernizing wholesale per se. We find that participation in the modernizing wholesale channel, relative to the traditional broker channel, requires greater land, regional, and nonland assets, as well as confers a premium controlling for quality, and spurs employment in harvesting and handling locally.